Multilevel analysis of the social determinants of health status and wellbeing of rural farmers in North-central Nigeria - Omoniwa, Adeyemi Esther; Babatunde, Raphael Olanrewaju; Uthman, Muhammed Mubashir; Alaba, Olufunke Aduke (Jabatan Kesihatan Masyarakat, Pusat Perubatan Universiti Kebangsaan Malaysia, 2016)
Introduction Over the years, rural dwellers have suffered from the unequal distribution of basic facilities when compared to the urban dwellers. This has resulted in situations where their health have been compromised and thus their productive capacity. Methods This paper using a Multilevel Analysis examines these social determinants of health status and wellbeing of rural farmers in North-central, Nigeria. Analytical tools employed include the descriptive statistics and the multivariate multilevel model. Results The result of the analysis showed that the income, years of schooling, living condition, frequency of physical exercise, alcohol consumption and smoking habit were some of the factors significantly influencing the health status and wellbeing of rural farmers in the study area. Others include exposure to tobacco smoke, access to improved toilet facilities, proper solid waste management and distance to potable water. It also revealed that community level co-variation between health status and wellbeing was stronger than at the individual level. Conclusions Therefore, it was recommended that efforts should be made by government to provide rural areas with basic potable water sources. The rural dwellers should also be enlightened on the basics of good sanitation and hygiene. This will help reduce diseases and deaths from water-related infections and poor hygiene. Furthermore, laws should be put in place to prohibit smoking of tobacco products in public places. All these will reduce the incidence of disease conditions thereby resulting in a healthier workforce that can thus work together with the government towards the achievement of the sustainable development goals.